Message - El-Fitiany, Rana Ahmed Mohammed El-Saied (Universal Journal of Pharmaceutical Research, 2018)
I would like to deeply congratulate all the Universal Journal of Pharmaceutical Research team for completing 3 successful years since the rise of the journal. It was an honor to join the UJPR team as a member in the Editorial Board team since 12th of October 2017. I am feeling comfort and satisfaction during my work with them as the entire team members are active, cooperative and helpful. I would like also to thank all editorial board members for providing the convenient atmosphere for raising proposals and suggestions to improve the journal quality, as consequence all the articles are having now DOI and the journal is indexed in Google scholar for example, which increase the journal articles citation. Thus, I’m very optimistic for the future of our journal as I am expecting much more progress for UJPR to be indexed in the important indexing platforms as Scopus and Thomson Reuters.